Development and application of a methodological tool for prioritization of rehabilitation of abandoned tailings dumps in the Giyani and Musina areas of South Africa. Issue 1 (1st January 2019) - Mhlongo, Sphiwe Emmanuel; Amponsah-Dacosta, Francis; Kadyamatimba, Armstrong
Abstract: South Africa has numerous voluminous tailings dumps that will certainly require rehabilitation. The aim of this work was to develop a methodological approach for prioritization of rehabilitation of abandoned tailings dumps. To test the applicability of the developed method in different conditions, it was applied on six abandoned tailings dumps denoted as FGMT, LMMT, KLMT, MCMT, NMMT-A and NMMT-B found in the Giyani and Musina areas of South Africa. The method involved integration of quantitative and qualitative techniques in making sound decision on the order of rehabilitation of the tailings dumps in the area. It considered the contamination potential of the dumps, the ease of their dispersion to the surroundings and the impact they have on the appearance of the natural landscape. The use of the tool on abandoned tailings dumps in the study area revealed that gold tailings dumps are to be rehabilitated first than magnesite and copper tailings dumps. The study indicated that the dump with the highest pollution potential was the FGMT and that physical stabilization was considered the most suitable rehabilitation option for abating its high toxic metals from polluting the environment. The combination of methods that improve physical stability of the dump while enhancing nutrient availability for plant growth were found appropriate for rehabilitation of MCMT. The rehabilitation of the rest of the dumps required the use of chemical methods that promote growth of vegetation. According to the study, the developed tool can be used to guide rehabilitation of abandoned tailings dumps in different settings.